Surgical Management of Trigeminal Neuralgia Emerging in the Long-Term after Cerebellopontine Angle Tumor Surgery without Tumor Regrowth - Matsushima, Ken; Matsunaga, Kyosuke; Ichimasu, Norio; Nakajima, Nobuyuki; Kohno, Michihiro (Journal of Neurological Surgery Part B: Skull Base, 2025)
Cerebellopontine angle tumors are reported causes of trigeminal neuralgia, but trigeminal neuralgia emerging long after cerebellopontine angle tumor removal, despite the absence of tumor regrowth, is extremely rare. Surgical resolution is required for intractable cases, but it is challenging due to the altered anatomy and severe adhesions from prior surgery, and unclear etiologies.Retrospective case series.About 2,580 patients underwent cerebellopontine angle tumor resection (including vestibular schwannomas, meningiomas, trigeminal schwannomas, epidermoid cysts, and others) during a 19-year period.Postoperative pain resolution and neurological complications after surgical intervention for trigeminal neuralgia without tumor regrowth.Three patients required surgical intervention for delayed-onset trigeminal neuralgia, occurring 2 to 11 years after the vestibular schwannoma surgery. In all patients, the offending artery was transposed, and thick arachnoid adhesions were dissected. Additional procedures included the separation of the compressing vein, the separation of the adhering facial nerve, and the removal of residual tumor to isolate the trigeminal nerve. All patients experienced complete pain relief postoperatively without developing new permanent neurological deficits, except for one patient who developed mild facial hypoesthesia.Although rare and technically challenging, surgical intervention can be an effective and safe treatment for surgery-associated trigeminal neuralgia. Comprehensive management of all possible etiologies, including separation of the surrounding structures (arteries, veins, cranial nerves, arachnoid, and residual tumor) from the trigeminal nerve, should be considered for complete and secure pain relief under detailed neuromonitoring.
Keywords: acoustic neuroma; functional neurosurgery; microvascular decompression; neurovascular compression syndromes; retrosigmoid lateral suboccipital approach